The mediating role of HR practices to enhance the innovative capabilities of SMEs - Siti Nur Azizah; Feby Evelyna (Institute of Computer Science (IOCS), 2024)
This research aims to determine the influence of organizational culture on innovative capabilities with human resource practices as a mediator. This quantitative descriptive research took the population of SME employees in Kebumen with the criteria of being a medium-sized business.Usually research on HR practices is carried out in large companies, but this research was carried out in SMEs that manage a minimum of 6-19 employees. The research results show that organizational culture does not influence innovative ability. However, HR practices that use the AMO concept have an impact on innovative capabilities. HR practices mediate the influence of organizational culture on innovative capabilities. This shows that through HR practices characterized by ability, motivation and opportunity, innovative capabilities can be increased. SME owners can benefit from good HR practice activities in their organization.